The tyrants - Foss, Clive (Quercus, 2006)
Profiles the lives and deeds of fifty dictators from around the world who have ruled at times throughout the past 2500 years, including Julius Caesar, Herod, Lenin, Stalin, Hitler and Saddam Hussein.